Approximate Accuracy Approaches to Attribute Reduction for Information Systems - Deshan Liu; Dapeng Wang; Deqin Yan; Yu Sang (Abstract and Applied Analysis)
The key problem for attribute reduction to information systems is how to evaluate the importance of an attribute. The algorithms are challenged by the variety of data forms in information system. Based on rough sets theory we present a new approach to attribute reduction for incomplete information systems and fuzzy valued information systems. In order to evaluate the importance of an attribute effectively, a novel algorithm with rigorous theorem is proposed. Experiments show the effect of proposed algorithm.